Feed lot and pasture-fattening tests with feeder lambs, 1957-58. Studies carried on by the Department of Animal Husbandry and the Garden City Branch Experiment Station. - Menzies, C.S.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2011)
Two lots of lambs were grazed on wheat pasture for the entire 123-day experimental period. Lambs in one of these, lot 5, were also shorn at the start of the test on November 7. One-third of the lambs in each lot received a 3-mg. stilbestrol implant, 1/3 received a 6-mg. stilbestrol implant and the remaining % served as the hormone control. Two lots of lambs were used in a combination feed-lot and wheat-pasture study. One of these lots was grazed on wheat pasture for 60 days and then was switched to the feed-lot for the remaining 63 days of the test. The second lot was started in the feed-lot and was then switched to wheat pasture. One-third of the lambs in these two lots were implanted with 3 mgs. stilbestrol, 1/3 received a 6-mg. stilbestrol implant and the remaining 1/3 received no hormone.
Keywords: Sheep; Stilbestrol implant; Aureomycin; Hydroxyzine tranquilizer